Autophagy and autophagic cell death in sepsis: friend or foe? - Toshiaki Iba; Julie Helms; Cheryl L. Maier; Ricard Ferrer; Jerrold H. Levy (Journal of Intensive Care)
Abstract In sepsis, inflammation, and nutrient deficiencies endanger cellular homeostasis and survival. Autophagy is primarily a mechanism of cellular survival under fasting conditions. However, autophagy-dependent cell death, known as autophagic cell death, is proinflammatory and can exacerbate sepsis. Autophagy also regulates various types of non-inflammatory and inflammatory cell deaths. Non-inflammatory apoptosis tends to suppress inflammation, however, inflammatory necroptosis, pyroptosis, ferroptosis, and autophagic cell death lead to the release of inflammatory cytokines and damage-associated molecular patterns (DAMPs) and amplify inflammation. The selection of cell death mechanisms is complex and often involves a mixture of various styles. Similarly, protective autophagy and lethal autophagy may be triggered simultaneously in cells. How cells balance the regulatory mechanisms of these processes is an area of interest that is still under investigation. Therapies aimed at modulating autophagy are considered promising. Enhancing autophagy helps clear and recycle damaged organelles and reduce the burden of inflammatory processes while inhibiting excessive autophagy, which could prevent autophagic cell death. In this review, we introduce recent advances in research and the complex regulatory system of autophagy in sepsis.